Postgraduate Students’ Individual Educational Paths: Design Principles and Implementation Conditions (on the Example of a Technical University) - A. S. Klimova; L. F. Krasinskaya (Высшее образование в России)
The article addresses the importance of introducing individual educational paths (IEP) in training research and pedagogical personnel in postgraduate studies. The idea of an individual approach of learning is enshrined in a number of documents including the Federal Law “On Education in the Russian Federation”. However, in practice, there are obstacles to the implementation of IEP: the presence of regulatory documents governing the organization of the educational process in higher education, the predominance of the group form of organizing classes, the unpreparedness of teachers for the implementation of the personalized learning model. We find it reasonable to start the implementation of IEP at the level of postgraduate training, given the relative small number of students, as well as their cognitive independence and well-developed educational skills. The design of the IEP will make it possible to better take into account the initial competencies of postgraduate students, their cognitive needs and goals in further career advancement (orientation towards teaching, research, production activities), which are largely determined by the nature and level of professional education.The article reveals the specifics of the training of research and pedagogical personnel in the postgraduate study of a technical university, identifies the factors that have an impact on the way postgraduate students build their learning trajectories, substantiates the principles of IEP design, and describes the stages of personalized learning technology. The research data on the readiness of postgraduate students to design IEP on their own are presented. The results of the survey of post graduate students and their supervisors indicate that there are sufficient grounds for the successful implementation of a personalized learning model using IEP. Postgraduate students of a technical university are well versed in information resources, actively use University’s services of the electronic educational environment. They are able to determine the goals of educational and scientific activities, assess their competencies, and analyze achievements and failures. Most of scientific advisors are ready to assist postgraduate students in IEP designing. The article analyzes the difficulties that universities may encounter when introducing a new teaching model, and substantiates the conditions for the successful implementation of IEP in postgraduate studies.